A chronology for North Sea Lobe advance and recession on the Lincolnshire and Norfolk coasts during MIS 2 and 6. Issue 5 (October 2019) - Evans, David J.A.; Roberts, David H.; Bateman, Mark D.; Ely, Jeremy; Medialdea, Alicia; Burke, Matthew J.; Chiverrell, Richard C.; Clark, Chris D.; Fabel, Derek
Abstract: During the last (MIS 2) and older glaciations of the North Sea, a North Sea Lobe (NSL) of the British-Irish Ice Sheet flowed onshore and terminated on the lowlands of eastern England, constructing inset sequences of either substantial ice-marginal deposits and tills or only a thin till veneer, indicative of complex and highly dynamic glaciological behaviour. The glaciation limit represented by the Marsh Tills and the Stickney and Horkstow Moraines in Lincolnshire is regarded as the maximum margin of the NSL during MIS 2 and was attained at ∼19.5 ka as determined by OSL dating of overridden lake sediments at Welton le Wold. A later ice marginal position is recorded by the Hogsthorpe-Killingholme Moraine belt, within which ice-walled lake plains indicate large scale ice stagnation rapidly followed ice advance at ∼18.4 ka based on dates from supraglacial lake deposits. The NSL advanced onshore in North Norfolk slightly earlier constructing a moraine ridge at Garrett Hill at ∼21.5ka. In addition to the large ice-dammed lakes in the Humber and Wash lowlands, we propose that an extensive Glacial Lake Lymn was dammed in the southern Lincolnshire Wolds by the NSL ice margin at the Stickney Moraine. Previous proposals that older glacier limits might be recorded in the region, lying between MIS 2 and MIS 12 deposits, are verified by our OSL dates on the Stiffkey moraine, which lies immediately outside the Garrett Hill moraine and appears to be of MIS 6 age.